Prevalence and Associated Factors of Dental Caries in Syrian Immigrant Children Aged 6-12 Years - Zeynep Meva Altaş; Mehmet Akif Sezerol (MDPI AG, 2023)
Immigrant children are among the groups that are sensitive to problems related to dental health. The aim of this study was to examine the dental caries of Syrian immigrant children. The study is a descriptive and retrospective study. Its population consists of Syrian immigrant children aged 6-12 years who were screened for dental health in the year 2022 in Istanbul. DMF-T (permanent teeth) and dmf-t (milk teeth) indices were used, which are the (t-T) criteria obtained by dividing the sum of caries (d-D), caries extracted (m-M) and caries-filled (f-F) teeth by the number of people examined. Higher dmft and DMFT scores indicate worse dental health. Dental screening was performed on 549 Syrian immigrant children. In total, 27.2% (n = 149) were brushing their teeth once a day and 97.3% of the children (n = 534) had at least one decayed tooth. The dmft score for the 6-7 year age (6.45 ± 3.33) group was significantly higher than the 8-9 year (4.98 ± 2.78) and 10-12 year (3.22 ± 2.02) age groups (p < 0.001). In our study, the dental caries were seen at a very-high frequency among immigrant children and the habit of tooth brushing remains at a low level. Lower age was the relevant factor for dental caries in our study.